2015
DOI: 10.24105/ejbi.2015.11.3.7
|View full text |Cite
|
Sign up to set email alerts
|

eHealth for Hearing - New Views and Apps Practicalities

Abstract: Background:We are observing a silent and disrupting revolution in the hearing health care practice due to the pervasive use of eHealth methods and technologies, in particular mobile apps. This situation is very new, e.g., in the novel interactions and relationship between actors, in the implicit knowledge relevant to actors, and in the acquisition and comprehension of health messages and fragmented, e.g., in knowledge, standardization, regulation, and in methods for quality evaluation, so here we propose a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The use of mobile devices and apps by health professionals in fields other than hearing care has been shown to support better clinical decision-making, greater engagement and improved patient outcomes (Ventola, 2014). As Tognola et al (2015) point out, hearing health care is undergoing a digital transformation with the increased use of eHealth technologies such as mobile apps. With the increase in smartphone and mobile device ownership in all age groups (Pew Research Center, 2015), hearing health care is well-positioned to harness the benefits that mobile apps can provide.…”
Section: Discussionmentioning
confidence: 99%
“…The use of mobile devices and apps by health professionals in fields other than hearing care has been shown to support better clinical decision-making, greater engagement and improved patient outcomes (Ventola, 2014). As Tognola et al (2015) point out, hearing health care is undergoing a digital transformation with the increased use of eHealth technologies such as mobile apps. With the increase in smartphone and mobile device ownership in all age groups (Pew Research Center, 2015), hearing health care is well-positioned to harness the benefits that mobile apps can provide.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of such apps identified 203 applications categorised as apps for screening and self-testing, education and information, assistive tools and mobile applications supporting users with easy ways to amplify sound [34]. However, eHealth solutions connecting key actors in hearing healthcare remain a vision, rather than current practice [7]; yet the scenario is presented as 'a silent and disrupting revolution in the hearing health care practice' offering opportunities for 'novel interactions and relationships between actors' [39]. Challenges in relation to eHealth solutions include adherence, quality, effectiveness and privacy [34].…”
Section: Hearing Applicationsmentioning
confidence: 99%
“…The portable and instant nature of mobile devices and applications can enable on-demand information and data sharing, and open up for an abundance of personalized mHealth solutions connecting different actors such as professionals, patients, families and significant others. Apps are frequently described as appealing to the tech-savvy generation of baby-boomers and could, together with online home-based rehabilitation, supplement the professional toolbox and enable patient-centred healthcare [ 5 , 7 , 21 ]. At the same time, the issues and challenges of mHealth in HHC are still a matter of debate and the clinical adoption of mobile solutions is rather limited [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of audiology, Cherry and Rubinstein suggested the use of eHealth for patient follow-up as early as in 1994 [ 20 ], introducing remote follow-up by telephone following face-to-face fittings of hearing aids (HAs). Use of eHealth has grown since then and, to date, several solutions are available for various hearing-related conditions (e.g., hearing loss (HL), tinnitus, balance problems) and for different target user groups (e.g., children with cochlear implants, parents of children with HL, adults fitted with HAs or implantable devices, older adults, patients suffering from tinnitus) [ 6 , 7 , 10 ]. Recently, the ecosystem of eHealth solutions has grown further and includes interesting developments in the field of mobile apps for patients and their families, for professionals, or for the general population [ 3 , 5 , 6 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation